Exploring the Impact of Personalized Principal Supervision on Teacher Development: A Novel Approach to Educational Leadership - Gunadi, Gugun; Lathifah, Zahra Khusnul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study examines the significance of personalized principal supervision in enhancing teacher performance in schools. This study aims to analyze how the personalized principal supervision model can improve teacher performance in schools. The research method employed is qualitative, utilizing a case study design. Data collection techniques involve interviews, observations, and documentation. Data analysis is carried out through data condensation, data display, and data verification. The results of the study indicate that an open relationship between the principal and teachers, along with providing clear and specific feedback, can enhance teacher competence. Training tailored to individual needs and a collaborative approach create a climate that supports professional development. The implications of this study suggest that personalized principal supervision can enhance teacher performance and foster their competency development. This study suggests that the implementation of personalized principal supervision can be an effective model for improving teacher performance. With a more adaptive and individualized approach, principals can strengthen teacher professional development, foster a more productive climate, and enhance the quality of learning in schools.